Cerebellar ataxia and ectodermal dysplasia in brothers. Issue 6 (June 1993) - Baraitser, M; Reardon, W; McShane, A; Wilson, J
Abstract : Two brothers are documented with an ectodermal dysplasia primarily involving the teeth and hair. Both have developed cerebellar ataxia in the early teens.